2020
DOI: 10.2147/cmar.s224067
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA MAGI2-AS3 Affects Cell Invasion and Migration of Cervical Squamous Cell Carcinoma (CSCC) via Sponging miRNA-233/EPB41L3 Axis</p>

Abstract: Introduction: The incidence of cervical squamous cell carcinoma (CSCC) has expanded in recent years. However, the function of long non-coding RNA (lncRNA) MAGI2-AS3 in the occurrence and progression of CSCC remains unclear. Therefore, the role of lncRNA MAGI2-AS3 in cervical squamous cell carcinoma (CSCC) was investigated in our study. Methods: We used qRT-PCR analysis to identify the level of MAGI2-AS3 mRNA expression in CSCC clinical samples and cell lines. We investigated cell migration and invasion of CSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Intriguingly, miR-223 was highly expressed in CC tissues, 15 and the increased expression of miR-223 in CC tissues was possibly modulated by the transcription factor STAT3. 16 Our prediction using the UCSC bioinformatics website and ChIP assay revealed that HDAC10 bound to the miR-223 promoter and positively regulated its acetylation level, indicating a novel acetylation-dependent regulation of miR-223 upregulation in CC.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, miR-223 was highly expressed in CC tissues, 15 and the increased expression of miR-223 in CC tissues was possibly modulated by the transcription factor STAT3. 16 Our prediction using the UCSC bioinformatics website and ChIP assay revealed that HDAC10 bound to the miR-223 promoter and positively regulated its acetylation level, indicating a novel acetylation-dependent regulation of miR-223 upregulation in CC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA MAGI2‐AS3 is a recently identified lncRNA, which has been widely examined as a tumor suppressor in various cancers, including hepatocellular carcinoma, bladder, lung, ovarian, cervical, and prostate cancers. 29 , 30 , 31 , 32 , 33 , 34 LncRNA MAGI2‐AS3 plasma levels have been evaluated in patients with IDD pre‐ and post‐treatment, and the findings indicated that patients with IDD were found to exhibit reduced lncRNA MAGI2‐AS3 expression, and its expression was significantly augmented after clinical treatments. 15 Herein, our results confirmed that lncRNA MAGI2‐AS3 expression was reduced in LPS‐triggered NP cells, and augmenting this expression could promote NP cell viability and ECM synthesis while suppressing apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA MAGI2‐AS3 is a recently identified lncRNA, which has been widely examined as a tumor suppressor in various cancers, including hepatocellular carcinoma, bladder, lung, ovarian, cervical, and prostate cancers 29–34 . LncRNA MAGI2‐AS3 plasma levels have been evaluated in patients with IDD pre‐ and post‐treatment, and the findings indicated that patients with IDD were found to exhibit reduced lncRNA MAGI2‐AS3 expression, and its expression was significantly augmented after clinical treatments 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prognostic value of MAGI2-AS3 was not statistically significant. Similarly, Hou et al evidenced a decreased accumulation of MAGI2-AS3 in cervix squamous cell carcinomas compared with control tissue [ 215 ]. They further demonstrated that MAGI2-AS3 inhibited SiHa and HeLa cell invasion and migration by sponging miR-223 leading to up-regulation of the tumor suppressor EPB41L3.…”
Section: Magi Cernas In Carcinogenesismentioning
confidence: 99%